On designing peer-to-peer systems over wireless networks. (16th July 2008) - Yan, Lu; Zhou, Xinrong
With the advance in wireless communication technology and the increasing number of mobile users, peer-to-peer computing, in both academic research and industrial development, has recently begun to extend its scope to address problems related to mobile devices and wireless networks. This paper is a performance study of peer-to-peer systems over wireless networks. We show that the crosslayer approach performs better than separating the overlay from the access networks with a comparison of different settings for the peer-to-peer overlay and underlaying wireless ad hoc network. We then present a performance model towards in-depth understanding of those systems. Our results provide useful guidelines for mobile operators, value-added service providers and application developers to design and dimension peer-to-peer systems over wireless networks.